Crystal structure of (2E)-1-(4-hydroxy-1-methyl-2-oxo-1, 2-dihydroquinolin-3-yl)-3-(4-hydroxy-3-methoxyphenyl)prop-2-en-1-one. (April 2015) - Kimpende, P. Mangwala; Nguyen, N. T.; Nguyen, M. T.; Vu, Q. T.; Meervelt, L. Van
No abstract available